Different regulation of P-glycoprotein function between Caco-2 and Caki-1 cells by ezrin, radixin and moesin proteins. (17th February 2016) - Yano, Kentaro; Otsuka, Kyoma; Kato, Yuko; Kawabata, Hideaki; Ohmori, Shinya; Arakawa, Hiroshi; Ogihara, Takuo
Abstract: Objectives: P-glycoprotein (P-gp) mediates efflux of many xenobiotics, including therapeutic drugs, from normal and tumour tissues, and its functional localization on the plasma membrane of cells is regulated by scaffold proteins, such as ezrin, radixin and moesin (ERM proteins). We previously reported that radixin is involved in post-translational regulation of P-gp in hepatocellular carcinoma HepG2 cells and mouse small intestine, but not in mouse kidney. Methods: Here, we investigated whether the role of ERM proteins in regulation of P-gp transport activity in cancers is the same as that in the corresponding normal tissues, using human colon adenocarcinoma (Caco-2) cells and renal carcinoma (Caki-1) cells. Key findings: In Caco-2 cells, radixin silencing alone reduced the P-gp-mediated intracellular accumulation of rhodamine123 (Rho123), while the mRNA level of P-gp was unchanged. Thus, it appears that only radixin among the ERMs regulates P-gp activity in Caco-2 cells. On the other hand, none of the ERM proteins influenced P-gp activity in Caki-1 cells. Conclusions: The regulation of P-gp by ERM proteins is different between Caco-2 and Caki-1 cells. Moreover, these regulatory properties are the same as those of the corresponding normal tissues, and suggest that tissue-specific differences in the regulation of P-gp by ERM proteins are retained in cancerous tissues.